2005
DOI: 10.1109/ted.2004.841264
|View full text |Cite
|
Sign up to set email alerts
|

Threshold voltage control in NiSi-gated MOSFETs through SIIS

Abstract: Complete gate silicidation has recently been demonstrated as an excellent technique for the integration of metal gates into MOSFETs. From the various silicide gate materials NiSi has been shown to be the most scalable. In this paper, a versatile method for controlling the workfunction of an NiSi gate is presented. This method relies on doping the poly-Si with various impurities prior to silicidation. The effect of various impurities including B, P, As, Sb, In, and Al is described. The segregation of the impuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…In the conventional P incorporation process, P ions are implanted into a poly-Si gate before Ni silicide gate formation and introduced to the Ni silicide/SiO 2 interface with the ''snow-plow effect'' during silicidation (pre-doping process). [1][2][3][4][5][6][7]12) However, not only P segregation but also changes in crystallinity and Ni-Si ratio of the silicide layer occur in the pre-doping process. 6,8) These changes of the film structure make it difficult to evaluate the unadulterated effect of P segregation, since they are also possible causes of È eff modulation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the conventional P incorporation process, P ions are implanted into a poly-Si gate before Ni silicide gate formation and introduced to the Ni silicide/SiO 2 interface with the ''snow-plow effect'' during silicidation (pre-doping process). [1][2][3][4][5][6][7]12) However, not only P segregation but also changes in crystallinity and Ni-Si ratio of the silicide layer occur in the pre-doping process. 6,8) These changes of the film structure make it difficult to evaluate the unadulterated effect of P segregation, since they are also possible causes of È eff modulation.…”
Section: Methodsmentioning
confidence: 99%
“…The observation that the slopes of V fb vs EOT relations are almost the same indicates little changes in fixed charge densities at the SiO 2 /Si(100) interface. In the Ni 2 Si (Ni 3 Si 2 )/SiO 2 and NiSi/SiO 2 systems, the V fb values shift to the negative direction and the evaluated È eff s from the y-intercept decrease with P segregation similarly to those of P pre-doped cases; 1,[4][5][6][7] the È eff changes from 4:70 AE 0:01 to 4:38 AE 0:01 eV at Ni 2 Si (Ni 3 Si 2 )/SiO 2 interface, and from 4:66 AE 0:01 to 4:37 AE 0:01 eV at the NiSi/SiO 2 interface. We found that È eff also decreases with P segregation in the NiSi 2 /SiO 2 system, and the largest ÁÈ eff of À0:45 eV was obtained with the realization of the lowest È eff value of 4:13 AE 0:04 eV, which is close to Si-E c suitable for nMOS devices.…”
Section: Dependence Of Phosphorous Segregated è Eff Modulation On Ni-...mentioning
confidence: 98%
See 2 more Smart Citations
“…[2][3][4] Ni-FUSI gate structure can be realized by modification of today's selfaligned silicidation technology without novel metaldeposition and gate-etching processes, resulting in reduced CMOS fabrication process complexity.…”
Section: Introductionmentioning
confidence: 99%